Modulated crystal structure of InMo4O6. Issue 4 (3rd August 2016) - Schultz, Peter; Simon, Arndt; Oeckler, Oliver
Abstract : Tetragonal InMo4 O6 is a metal‐rich compound with infinite chains of edge‐sharing Mo6 clusters; the (3 + 1)‐dimensional modulated structure hosts In6 and In7 oligomers in channels along [001] – this leads to two different kinds of disorder. Abstract : The (3 + 1)‐dimensional modulated crystal structure of the metal‐rich cluster compound InMo4 O6 was solved and refined from single‐crystal data in the superspace group P 4/ mbm (00γ)00 ss [q = 0, 0, 0.1536 (4); a = 9.6664 (9), c = 2.8645 (3) Å; R 1(all) = 0.046, wR (all) = 0.076]. The crystal structure is closely related to the NaMo4 O6 structure type. It is built from rods of Mo6 clusters condensed via trans edges. These form channels parallel to [001], in which In6 and In7 oligomers alternate. Weak diffuse planes parallel to (001)* interconnect the satellite reflections; they occur due to two‐dimensional rod disorder of the In oligomer chains.